Reliability and minimal detectable change of sprint times and force-velocity-power characteristics - Edwards, T.; Banyard, H. G.; Piggott, B.; Haff, G. G.; Joyce, C. (The Journal of Strength and Conditioning Research, 2022)
Research has not yet provided critical information for practitioners to determine the minimal detectable change (MDC) in sprint times or force-velocity-power characteristics. Therefore, the aim of this study was to establish the interday reliability and MDC of sprint times and sprint force-velocity-power characteristics in junior Australian football (AF) players. Seventeen players were assessed using a radar device that recorded instantaneous velocity during 3 maximal 30-m sprint accelerations performed on 2 nonconsecutive days. Sprint force, velocity, and power characteristics were derived through inverse dynamics applied to the raw velocity-time data. Relative and absolute reliability was determined by calculating the intraclass correlation coefficient (ICC), coefficient of variation (CV), and MDC. Data analysis was assessed for (a) the first trial, (b) the best trial (the fastest 30-m split time), (c) the average of the first 2 trials, and (d) the average of all 3 trials from each testing session. The main findings were (a) absolute theoretical maximum force (F0), theoretical maximal velocity (V0), absolute and relative maximum power (Pmax), maximum ratio of force (RFmax), maximum velocity (Vmax), and all sprint distance times (5-30 m) displayed acceptable reliability (CV < 10% and ICC >0.75) and 2) the average of 2 and 3 trials was the best method of establishing reliable sprint times and force-velocity-power characteristics between sessions. This study provides important information for practitioners to determine the MDC in sprint times and force-velocity-power characteristics that allow coaches to identify true changes in performance.